Conjugated Polymer Shells on Colloidal Templates by Seeded Suzuki–Miyaura Dispersion Polymerization. Issue 5 (13th November 2013) - ten Hove, Jan Bart; Appel, Jeroen; van den Broek, Johanna M.; Kuehne, Alexander J. C.; Sprakel, Joris
<x xml:space="preserve">Abstract</x> The self‐assembly of colloidal conjugated polymers presents a versatile and powerful oute towards new functional optoelectronic materials and devices. However, this strategy relies on the existence of chemical protocols to prepare highly monodisperse colloids of conjugated polymers in high yields. Here, a recently developed Suzuki–Miyaura dispersion polymerization method is adopted to synthesize core–shell particles, in which a conjugated polymer shell is grown onto non‐conjugated organic and inorganic colloidal templates. By chemically anchoring aryl halide groups at the particle surface, a conjugated polymer shell can be attached to a wide variety of organic and inorganic microparticles. In this way, both spherical and non‐spherical hybrid conjugated polymer particles are prepared, and it is shown that the method can be applied to a variety of conjugated polymers. This new method offers independent control of the size, shape and photophysical properties of these novel conjugated polymer particles.